2017
DOI: 10.18632/oncotarget.20244
|View full text |Cite
|
Sign up to set email alerts
|

CD163 as a novel target gene of STAT3 is a potential therapeutic target for gastric cancer

Abstract: CD163 is a member of the scavenger receptor cysteine-rich superfamily, and has been widely used to identify M2 type macrophage. However, the expression of CD163 in gastric cancer and its regulatory mechanism are still unclear. Here we show that CD163 is elevated in gastric cancer tissues. High expression of CD163 is a potential indicator to evaluate the status of tumor associated macrophages (TAMs), regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs) and cancer associated fibroblasts (Cafs). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…We have also detected an enrichment on the macrophage chemotaxis protein set. Therefore, our results suggest that both regulatory macrophages and dexa-tolDC might be triggering similar tolerogenic mechanisms, probably through the STAT3 and Wnt5a signaling pathway, as its interaction with CD163 has already been reported in cancer studies 31 , 32 . Regarding C1QB and C1QC genes, their overexpression is aligned with the up-modulation of the complement activation protein set.…”
Section: Discussionsupporting
confidence: 69%
“…We have also detected an enrichment on the macrophage chemotaxis protein set. Therefore, our results suggest that both regulatory macrophages and dexa-tolDC might be triggering similar tolerogenic mechanisms, probably through the STAT3 and Wnt5a signaling pathway, as its interaction with CD163 has already been reported in cancer studies 31 , 32 . Regarding C1QB and C1QC genes, their overexpression is aligned with the up-modulation of the complement activation protein set.…”
Section: Discussionsupporting
confidence: 69%
“…[33][34][35] Furthermore, we also found that CD163 was positively associated with fibroblasts ( Figure 4(a,b), lower panel), which was consistent with the previous reports that the expression of CD163 was positively associated with fibroblasts. [36][37][38] These data suggested that CD163 may participate in the regulation of stromal cells in the tumor microenvironment.…”
Section: Relationship Between Cd163 and Infiltrated Cells In The Tumomentioning
confidence: 80%
“…However, in the tumor microenvironment, macrophages are also known to produce inflammatory mediators and reactive oxygen species that can induce angiogenesis and promote tumor progression [30][31][32]. To investigate the M2/antiinflammatory macrophage distribution in KS tissues, we evaluated the distribution of CD163, a hemoglobinhaptoglobin acute phase marker which is often correlated with myeloid suppressor phenotypes [33]. While CD163 + myeloid cells were evident in biopsied tissue, the majority were localized in LANAregions (P = 0.0002) ( Figure 6A and 6B).…”
Section: Cd163 Expressing Cells Are In Lana Negative Regionmentioning
confidence: 99%